AN ANALYSIS OF DEIXIS IN BEAUTY AND THE BEAST MOVIE - Ni Luh Dewi Widiari; Ni Luh Nyoman Seri Malini; I Gusti Ngurah Parthama (ELTIN Journal, 2024)
This research explores how the context of an utterance affects the interpretation of dialogue. The focus is on analyzing the different types of deixis and their functions within the film's conversations. Using a qualitative descriptive approach, the study collects data from the movie's dialogue through documentation and note-taking. The analysis is grounded in Levinson's Theory, identifying five categories of deixis: person, time, place, social, and discourse. Each type serves a distinct function: person deixis is reflected in personal pronouns, place deixis in locative adverbs, time deixis in temporal adverbs, social deixis through relational markers, and discourse deixis as demonstrated by demonstrative pronouns.